Sistem Penyimpanan Arsip Untuk Meningkatkan Pelayanan Publik di Kantor Desa Plelen - Mulyapradana, Aria; Kharis, Aghus Jamaludin; Muafiq, Farikul; Paramita, Intan Indi; Lestari, Madina Cahya (Universitas Indo Global Mandiri, 2023)
Archives are very important for any organization or company. The purpose of this study was to determine the archive storage system and public services at the Plelen Village Office. This study used triangulation and qualitative description. This research was conducted at the Plelen Village Office and used primary and secondary data. The village head, village secretary and three village officials were informants for this research. The result of this research is that the archive storage system at the Plelen Village Office has been running quite well but still needs to be improved because the archive storage system is still manual, the number of archives created is not proportional to the area where archives are stored, it is necessary to add archive equipment to store archives and start switching to using information technology, one of which is Google Drive which is a solution to archive storage. The use of Google Drive at the Plelen Village Office has not been utilized optimally due to the limited number of human resources who handle archives, providing archival training and information technology to village officials which are not routinely carried out so that there is a lack of knowledge and skills in archive storage. Therefore, the provision of training on records management and digitization needs to be scheduled so that records managers can manage their records properly and the quality of public services and the image of the organization is well maintained.